2020
DOI: 10.14814/phy2.14640
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of chemokine production in bovine endometrial epithelial and stromal cells under heat stress conditions

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 49 publications
(66 reference statements)
1
9
0
Order By: Relevance
“…To recover from endometritis, endometrial epithelial and stromal cells secrete the IL‐6 to recruit macrophages into infection site, to induce the inflammation, and to activate the neutrophils (Ataie‐Kachoie et al, 2014; Clahsen & Schaper, 2008; Hurst et al, 2001; Jones et al, 2006; Saut et al, 2014; Sheldon et al, 2014). Recent our study showed that hyperthermia induces the IL6 mRNA expression and IL‐6 secretion responsive to LPS in the bovine endometrial stromal cells while those in the bovine endometrial epithelial cells are suppressed, and consequently affects the localization of macrophages in the endometrium (Sakai et al, 2020). Here, we focused on the mechanisms for the alteration of IL‐6 production in the two types of endometrial cells in the presence of LPS under hyperthermia conditions.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…To recover from endometritis, endometrial epithelial and stromal cells secrete the IL‐6 to recruit macrophages into infection site, to induce the inflammation, and to activate the neutrophils (Ataie‐Kachoie et al, 2014; Clahsen & Schaper, 2008; Hurst et al, 2001; Jones et al, 2006; Saut et al, 2014; Sheldon et al, 2014). Recent our study showed that hyperthermia induces the IL6 mRNA expression and IL‐6 secretion responsive to LPS in the bovine endometrial stromal cells while those in the bovine endometrial epithelial cells are suppressed, and consequently affects the localization of macrophages in the endometrium (Sakai et al, 2020). Here, we focused on the mechanisms for the alteration of IL‐6 production in the two types of endometrial cells in the presence of LPS under hyperthermia conditions.…”
Section: Discussionmentioning
confidence: 95%
“…Recent our study showed that hyperthermia induces the IL6 mRNA expression and IL-6 secretion responsive to LPS in the bovine endometrial stromal cells while those in the bovine endometrial epithelial cells are suppressed, and consequently affects the localization of macrophages in the endometrium (Sakai et al, 2020). Here, we focused on the mechanisms for the alteration of IL-6 production in the two types of endometrial cells in the presence of LPS under hyperthermia conditions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations